The Perils of 'As If' European Constitutionalism†. Issue 5 (September 2016) - Lindseth, Peter L.
Abstract: This review article offers thoughts on Kaarlo Tuori's recent book, European Constitutionalism, and more particularly on what he calls the 'disciplinary contest over the legal characterisation of the EU and its law'. As the book's title suggests, Tuori privileges the constitutional perspective in that contest, so much so—he freely admits—that his analysis 'predetermine[s] how the EU and its law will be portrayed'. And therein also lies the book's main weakness. Tuori's predetermined 'constitutional' interpretation, like so much of the dominant legal discourse in the EU today, ultimately obscures the core contradiction in EU public law. National institutions are increasingly constrained in the exercise of their own constitutional authority but supranational institutions are unable to fill the void because Europeans refuse to endow them with the sine qua non of genuine constitutionalism: the autonomous capacity to mobilise fiscal and human resources in a compulsory fashion. The EU's lack of constitutional power in this robust sense derives from the absence of the necessary socio‐political underpinnings for genuine constitutional legitimacy—what we can call the power‐legitimacy nexus in EU public law. To borrow Tuori's own evocative phrase, the EU possesses at best a 'parasitic legitimacy' derived from the more robust constitutionalism of the Member States as well as from the positive connotations that using 'constitutional' terminology evokes regardless of its ultimate aptness. The result is an 'as if' constitutionalism, the core feature of which is an increasingly untenable principal‐agent inversion between the EU and the Member States, one with profound consequences for the democratic life of Europeans. The sustainability of integration over the long term depends on confronting these adverse features of 'European constitutionalism' directly, something that legal elites—whether EU judges, lawyers, or legal scholars—ignore at their peril.